Programmed cell death in Leishmania: biochemical evidence and role in parasite infectivity - Gannavaram, Sreenivas; Debrabant, Alain (Frontiers in Cellular and Infection Microbiology, 2012)
Demonstration of features of a programmed cell death (PCD) pathway in protozoan parasites initiated a great deal of interest and debate in the field of molecular parasitology. Several of the markers typical of mammalian apoptosis have been shown in Leishmania which suggested the existence of an apoptosis like death in these organisms. However, studies to elucidate the downstream events associated with phosphotidyl serine exposure, loss of mitochondrial membrane potential, cytochrome c release, and caspase-like activities in cells undergoing such cell death remain an ongoing challenge. Recent advances in genome sequencing, chemical biology should help to solve some of these challenges. Leishmania genetic mutants that lack putative regulators/effectors of PCD pathway should not only help to demonstrate the mechanisms of PCD but also provide tools to better understand the putative role for this pathway in population control and in the establishment of a successful infection of the host.